PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KABUPATEN TOJO UNA-UNA - Umala, Muhajir (Katalogis, 2017)
The study aims to determine and analyze simultaneous and partial influence of leadership style, organizational culture, and work discipline on officials’ performance in The Department of Education, Youth, and Sports of Tojo Una-Una District. Type of study is descriptive causal. Population consists of 80 officials in The Department of Education, Youth, and Sports of Tojo Una-Una District, civil servants and honorer. Sample involves 44 people selected through proportionate random sampling. Method of analysis is multiple linear regressions. The test result finds that Fvalue=10.032 with sig.value of 0.000 on confidence level (α = 0,05). This proves that leadership style, organizational culture, and work discipline simultaneosly influence officials’ performance in The Department of Education, Youth, and Sports of Tojo Una-Una District, positively and significantly. Partially, leadership style and work discipline have positive and significant influence on performance, while work culture has positive but insignificant influence on officials’ performance in The Department of Education, Youth, and Sports of Tojo Una- Una District.